From Graphic Design to Communication in the Exhibition Context: A Virtual Approach - Gil Muñoz de la Nava, Nerea; Suárez Fernández, Marina; Cerezuela Sáenz de Buruaga, Guadalupe (Eikón / Imago, 2019)
Graphic design is as common as unnoticed. From this paradox it arises the necessity for its upgrade. Referring to its most primal function, of communicating, this article proposes to consider the concept from its base with the objective of generating new strategies that awaken interest in the audiences and multiply the possibilities of the exhibition in terms of dialectical experience. For this purpose visual arts serve as an inspiration and new technologies allow us to experiment with the design and creation of exhibition spaces.